Impact of quantization algorithm and number of gray level intensities on variability and repeatability of low field strength magnetic resonance image-based radiomics texture features. (December 2020) - Simpson, Garrett; Ford, John C.; Llorente, Ricardo; Portelance, Lorraine; Yang, Fei; Mellon, Eric A.; Dogan, Nesrin
Highlights: Low field strength magnetic resonance images are being utilized for patient set up. These daily images may contain prognostic data extractable using texture analysis. No consensus exists on preprocessing parameters for extraction for texture features. In a texture phantom: investigate impact of parameter selection on variability. In patient data: investigate impact of parameter selection on repeatability. Abstract: Purpose: The purpose of this work was to investigate the impact of quantization preprocessing parameter selection on variability and repeatability of texture features derived from low field strength magnetic resonance (MR) images. Methods: Texture features were extracted from low field strength images of a daily image QA phantom with four texture inserts. Feature variability over time was quantified using all combinations of three quantization algorithms and four different numbers of gray level intensities. In addition, texture features were extracted using the same combinations from the low field strength MR images of the gross tumor volume (GTV) and left kidney of patients with repeated set up scans. The impact of region of interest (ROI) preprocessing on repeatability was investigated with a test-retest study design. Results: The phantom ROIs quantized to 64 Gy level intensities using the histogram equalization method resulted in the greatest number of features with the least variability. There was no clear method that resulted in the highest repeatability in the GTV or left kidney. However, eight texture features extracted from the GTV were repeatable regardless of ROI processing combination. Conclusion: Low field strength MR images can provide a stable basis for texture analysis with ROIs quantized to 64 Gy levels using histogram equalization, but there is no clear optimal combination for repeatability.